A Conceptualization of the Experiences of Nursing Faculty who Supervise Master’s Thesis Research in Graduate Nursing Programs - Nakayama, Toshiko; Funashima, Naomi (Journal of Japan Society of Nursing Research, 2023)
Objective: To create concepts to describe the experiences of nursing faculty who supervise master's thesis research in Japanese graduate nursing programs. Methods: Methodology for conceptualization of Nursing was adopted. Through semi-structured interviews, data were collected from 10 nursing faculty who supervise master's theses research in Japanese graduate nursing programs. Data collection was completed by confirming saturation. The data were analyzed qualitatively, and the analysis was repeated until the researchers reached consensus, thus enhancing the study's trustworthiness. Results: All 10 subjects were female, with an average of 7.7 years' (SD=5.3) experience of supervising master's thesis research, and the number of graduates ranged between 1 and 15. Twenty-six concepts emerged as describing the nursing faculty's experience of supervising master's thesis research. These included 'in-class instruction and tutoring for completion of the master's thesis,' 'provision of preparatory information and assignment of assistants to graduate students to implement an efficient transition at each stage of their research.' Conclusions: Nursing faculty can use the 26 concepts to objectively understand their own supervision of master's theses research and as a basic resource for improving their research supervision.